Knowledge, attitude and practices of community health workers on managing and preventing childhood malaria and diarrhea in Fako Division, South West Region, Cameroon; A mixed method study - Ndum Naomi Chi; Raymond Babila Nyasa; Akoachere Jane-Francis (Public Library of Science (PLoS), 2023)
In developing countries, childhood malaria and diarrhea are among the 5 leading causes of death among children under five years; the use of community health workers (CHWs) to manage these diseases has shown some degree of success. A descriptive cross-sectional study was conducted to assess knowledge, attitude and practices (KAP) of CHWs on the management and prevention of childhood malaria and diarrhea in Fako Division, South-West Region, Cameroon. A pretested questionnaire was administered to eighty CHWs in Fako Division. Three focus group discussions (FGDs) were conducted with 29 CHWs. The Chi-Square and Spearman Correlation tests were used to investigate the association between socio-demographic characteristics with CHWs' KAP on childhood malaria and diarrhea management and prevention. A total of 52.5% of the participants had good knowledge, negative attitudes (65.0%), and carried out poor practices (60.0%) on the management and prevention of childhood malaria. Up to 8.75% CHWs did not know the first-line antimalarial drug used in Cameroon. More than half (57.5%) of participants had poor knowledge, 70.0% had a negative attitude and 82.25% carried out good practices on the management and prevention of childhood diarrhea. 47.6% of CHWs used a mixture of guava leaves and 'masepo' (Ocimum gratissimum) as treatment for childhood diarrhea. Level of education (p = 0.028) and Health District (p = 0.026) were significantly associated with practices on management and prevention of childhood diarrhea. CHWs had inadequate knowledge, poor attitude, and practices on childhood malaria management. Even though a majority of CHWs carried out good practices for diarrhea management, their knowledge and attitude were poor. Therefore, there is a need for training to improve CHWs' knowledge, attitude and practices on childhood malaria and diarrhea management.